2003
DOI: 10.1017/s0272263103000172
|View full text |Cite
|
Sign up to set email alerts
|

A Subject-Object Asymmetry in the Acquisition of Relative Clauses in Korean as a Second Language

Abstract: A variety of studies have reported that learners of English as a second language find subject relative clauses easier to produce and comprehend than direct object relatives, but it is unclear whether this preference should be attributed to structural factors or to a linear distance effect. This paper seeks to resolve this issue and to extend our understanding of SLA in general by investigating the interpretation of subject and direct object relative clauses by English-speaking learners of Korean, a left-branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
3
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 16 publications
2
71
3
2
Order By: Relevance
“…Similarly, hypotheses that predict complexity in terms of structural distance, such as the Structural Distance Hypothesis (O'Grady et al 2003), predict that like in SVO languages, SRs will be easier than ORs in an SOV language like Basque. However, the findings of the present experiment do not support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, hypotheses that predict complexity in terms of structural distance, such as the Structural Distance Hypothesis (O'Grady et al 2003), predict that like in SVO languages, SRs will be easier than ORs in an SOV language like Basque. However, the findings of the present experiment do not support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in L2 acquisition studies it has been reported that the performance on SRs is better than on ORs (Gass 1979(Gass , 1980(Gass , 1982Eckman et al 1988;Doughty 1991;Wolfe-Quintero 1992;Hamilton 1994Hamilton , 1995O'Grady 1999;O'Grady et al 2003).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Interestingly, wrong head errors have also been observed to occur in adult second language learners. Specifically, native English speaking adults acquiring Korean as a second language make wrong head errors in both their comprehension and production of Korean relative clauses (O'Grady, Lee, & Choo, 2003;O'Grady, Yamashita, Lee, Choo, & Cho, 2000). Such errors are particularly common when the target structure is an OG relative clause.…”
Section: Relative Clauses In Young Unimpaired Childrenmentioning
confidence: 99%
“…Keenan and Comrie (1977) found that relative clauses are constructed in a hierarchy called Noun Phrase Accessibility Hierarchy. Another hypothesis regarding RCs is Linear Distance Hypothesis (LDH) (Hawkins, 1989;O'Grady, Lee & Choo, 2003;Tarollo & Myhill, 1983) that maintains that the number of the intervening words between the head and the gap helps the prediction of accessibility. Structural Distance Hypothesis (SDH) alleges that structural distance between the nodes may explain the accessibility difficulty (O'Grady (1999).…”
Section: Introductionmentioning
confidence: 99%